Florida 4-H Cloverbud Project Report - Laura Cash; Geralyn Sachs; Christopher DeCubellis; Marnie Ward; Dallas Meringolo; Sarah Thomas Hensley; Andrew Toelle; Laura Valencia (EDIS)
The 4-H Cloverbud Project Summary is intended for youth ages 5–7 to complete at the completion of a 4-H educational project. This 7-page revision was compiled by the Florida 4-H Awards and Recognition Task Force; Geralyn Sachs and Laura Cash, chairs. https://edis.ifas.ufl.edu/4h032